Antigenicity analysis of human parvovirus B19-VP1u protein in the induction of anti-phospholipid syndrome. Issue 1 (1st January 2018) - Lin, Chun-Yu; Chiu, Chun-Ching; Cheng, Ju; Lin, Chia-Yun; Shi, Ya-Fang; Tsai, Chun-Chou; Tzang, Bor-Show; Hsu, Tsai-Ching
ABSTRACT: Mounting evidence suggests a connection between human parvovirus B19 (B19) and autoimmune diseases, and especially an association between the B19-VP1 unique region (VP1u) and anti-phospholipid syndrome (APS). However, little is known about the antigenicity of B19-VP1u in the induction of APS-like syndrome. To elucidate the antigenicity of B19-VP1u in the induction of APS, N-terminal truncated B19-VP1u (tVP1u) proteins were prepared to immunize Balb/c mice to generate antibodies against B19-tVP1u proteins. The secreted phospholipase A2 (sPLA2) activities and binding specificity of mice anti-B19-tVP1u antibodies with cardiolipin (CL) and beta-2-glycoprotein I (β2GPI) were evaluated by performing immunoblot, ELISA and absorption experiments. A mice model of passively induced APS was adopted. Although sPLA2 activities were identified in all B19-tVP1u proteins, only amino acid residues 61–227 B19-tVP1u exhibited a higher sPLA2 activity. Autoantibodies against CL and β2GPI exhibited binding activities with all B19-tVP1u proteins. IgG that was purified from mice that had been immunized with amino acid residues 21–227 to 121–227 B19-tVP1u proteins exhibited significantly higher binding activity with CL. IgG that was purified from mice that had been immunized with amino acid residues 21–227, 31–227, 82–227 and 91–227 B19-tVP1u proteins exhibited significantly higher binding activity with β2GPI. Accordingly, significantly higher binding inhibition of CL was detected in the presence of amino acid residues 61–227 and 101–227 B19-tVP1u. Significantly higher binding inhibition of β2GPI was detected in the presence of amino acid residues 21–227, 31–227, 82–227 and 91–227 B19-tVP1u. The mice that received amino acid residues 31–227 or 61–227 anti-tB19-VP1u IgG revealed significant thrombocytopenia and those that received amino acid residues 21–227, 31–227, 61–227, 71–227, 82–227, 91–227, 101–227 or 114–227 anti-tB19-VP1u IgG exhibited significantly prolonged aPTT. These findings provide further information concerning the role of B19-VP1u antigenicity in APS-like autoimmunity.